Role of Cations in Accumulation and Release of Phosphate by Acinetobacter Strain 210A - van Groenestijn, Johan W. (1988)
Cells of the strictly aerobic Acinetobacter strain 210A, containing aerobically large amounts of polyphosphate (100 mg of phosphorus per g [dry weight] of biomass), released in the absence of oxygen 1.49 mmol of P(i), 0.77 meq of Mg(2+), 0.48 meq of K(+), 0.02 meq of Ca(2+), and 0.14 meq of NH(4)(+) per g (dry weight) of biomass. The drop in pH during this anaerobic phase was caused by the release of 1.8 protons per PO(4)(3−) molecule. Cells of Acinetobacter strain 132, which do not accumulate polyphosphate aerobically, released only 0.33 mmol of P(i) and 0.13 meq of Mg(2+) per g (dry weight) of biomass but released K(+) in amounts comparable to those released by strain 210A. Stationary-phase cultures of Acinetobacter strain 210A, in which polyphosphate could not be detected by Neisser staining, aerobically took up phosphate simultaneously with Mg(2+), the most important counterion in polyphosphate. In the absence of dissolved phosphate in the medium, no Mg(2+) was taken up. Cells containing polyphosphate granules were able to grow in a Mg-free medium, whereas cells without these granules were not. Mg(2+) was not essential as a counterion because it could be replaced by Ca(2+). The presence of small amounts of K(+) was essential for polyphosphate formation in cells of strain 210A. During continuous cultivation under K(+) limitation, cells of Acinetobacter strain 210A contained only 14 mg of phosphorus per g (dry weight) of biomass, whereas this element was accumulated in amounts of 59 mg/g under substrate limitation and 41 mg/g under Mg(2+) limitation. For phosphate uptake in activated sludge, the presence of K(+) seemed to be crucial.